Predictors of forensic CBT group attendance and program completion. Issue 3 (3rd July 2019) - Hohman, Melinda; McDaniel, Erica; Twitchell, Geoffrey R.
ABSTRACT: With the increased focus on rehabilitation, county probation agencies may contract with community-based programs to provide treatment services. Forensic Cognitive Behavioral Therapy (F-CBT) is often used in group work to address probation client risk factors and prevent recidivism. This study examined demographic and risk factors of 534 adult probation clients referred to an F-CBT program to determine predictors of program intake, participation, and completion. Results showed that probation type, higher risk neighborhood of residence, and recidivism risk score were predictors of intake completion, but only recidivism risk scores predicted program completion. Implications and methods to increase program engagement are discussed.